Effect of Simple Oral Dental Extraction on Systemic Serum Amyloid A Concentrations in Horses - Amelia E. Sidwell; Marco Duz; Adeel Khan; Ronald Bodnàr; Sam Luis Hole (Veterinary Medicine and Science)
ABSTRACT Background The translocation of gingival commensals resulting in measurable systemic inflammation has been described in humans and non‐equine veterinary species with dental disorders, particularly periodontal disease. Routine odontoplasty does not result in increased serum amyloid A (SAA) concentration in horses, but a measurable increase in SAA concentration in horses undergoing dental extractions could suggest that local inflammation resulting from more severe dental disease has potential for wider, systemic consequences that warrants further study. Objectives To determine whether SAA increases in horses undergoing simple, oral extraction of non‐fractured cheek teeth with and without periodontal disease. Study Design Prospective cohort study. Methods SAA was measured using a stall‐side test in horses undergoing simple oral extraction of cheek teeth with intact clinical crowns at baseline (T = 0), 24 h (T = 24) and 48 h (T = 48) post‐extraction. Results Eight horses and 4 ponies aged between 4 and 23 years underwent cheek tooth extraction. A statistically significant difference in SAA concentration was noted between groups with and without periodontal disease at both 24 h (p = 0.004) and 48 h (p = 0.043). At 24 h, the median SAA concentration was 135 mg/L (range: 0–260 mg/L; IQR: 77.5–174 mg/L) in horses with periodontal disease and 27.5 mg/L (range: 0–47 mg/L; IQR: 4.8–43.5 mg/L) in horses without periodontal disease. At 48 h, median SAA concentration was 264 mg/L (range: 236–440 mg/L; IQR: 245.5–300.5 mg/L) in horses with periodontal disease and 0 mg/L (range = 0–41 mg/L; IQR: 0–21.8 mg/L) in horses without periodontal disease. Main Limitations Small sample group. Horses undergoing extraction of fractured cheek teeth were not included. Conclusions Extraction of non‐fractured cheek teeth does not result in a remarkable increase in SAA, except in horses with periodontal disease. These results suggest that periodontal disease in horses is associated with a local inflammatory response, which in turn drives the development of systemic inflammation, resulting in detectable increases in inflammatory markers when diseased periodontal tissues are disturbed.